PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA PADA MATERI ARITMATIKA SOSIAL - Kumaralo, Asti Ananta; Ismail, Sumarno; Usman, Kartin (Universitas PGRI Sumatera Barat, 2025)
This study aims to determine the effect of the problem-based learning model on students' mathematical problem-solving abilities in the social arithmetic materialThis study is an experimental study with a post-test only control group design. The sample in this study was class VII-A and VII-B at MTs Negeri 2 Kab. Gorontalo with a simple random sampling technique. The research instrument used was a problem-solving ability test on the Social Arithmetic material. The results of the study showed that there was an effect of problem-based learning on students' mathematical problem-solving abilities in the social arithmetic material, where the hypothesis testing using the t-test obtained a t-count value > t-table, namely 10.73 > 1.69. So it can be concluded that learning mathematics on the subject of social arithmetic using the problem-based learning model has a significant effect on improving students' mathematical problem-solving abilities compared to those using direct learning. So from what has been obtained, teachers can use the problem-based learning model as an effort to improve students' mathematical problem-solving abilities.